Where Does the Patient Fit? An Analysis of Word Use Within the Context of Interprofessional Collaborative Care. (December 2019) - Engel, Joyce; Prentice, Dawn; Hicks, Rachel
Patient-centeredness is considered central to interprofessional collaborative patient care as a participatory, partnered approach between health care professionals and patients. Content analysis of 501 articles from the 1986, 1987, 1988, 1996, 2006, 2013, 2014, and 2018 volumes of a selected journal was undertaken. The purposes were to identify contexts in which the term patient was used in articles with a primary focus on interprofessional care and to identify trends in its usage. With Dilthey's ideas on language as a framework, patient and its variations in the articles were coded under five categories. Findings suggest that the term patient appears predominantly as a modifier for activities enacted by experts and a platform for the discussion of relationships among professionals. There is limited evidence that use of the term patient fits within the context of partnership, suggesting that the language in published interprofessional collaborative research and discussion is currently largely expert, not patient-centered.